ANALISIS PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI ( Studi Pada Kantor Dinas Pariwisata Kabupaten Kutai Barat) - Paramita, Rosma (PREDIKSI, 2015)
ABSTRACKÂ Â Effect of Motivation on Employee Performance In Provincial Revenue Office of East Kalimantan.The purpose of this study was to determine whether there is influence of motivation on employee performance at the Provincial Revenue Office of East Kalimantan. The analysis tool used is the Simple Linear Regression. Sampling using the specified method, with a total sample of 45 employees of the Office of East Kalimantan Provincial Revenue from data obtained through questionnaires.Simple regression analysis results between employee motivation and performance variables obtained by the equation Y = 1.83 + 0.5127 X. Further correlation r value of 0.616. After the results of the analysis are compared with the r table (table critical value) where N = 45 with a significance level of 0.05, it turns out empirical count r is greater than r table (0.616> 0.3059). Thus the working hypothesis (hi) be accepted as true and reject the null hypothesis (ho). This means that there is influence between employee motivation employee performance at the Provincial Revenue Office of East Kalimantan.